Training in using maple and geogebra software for mathematics teachers in the environment SMA Negeri 15 Medan - Syahmarani, Aghni; Nasution, Putri Khairiah (Talenta Publisher, 2020)
Currently there are lots of softwares to solve problems including math problems. Mathematics teachers are now starting to be demanded to be able to operate some mathematical software to be considered capable of adapting to scientific developments, especially information technology at this time. For this reason training is needed for mathematics teachers so that they can master some mathematical software so that they become professional and more competent teachers. Dedication to this community will provide training to mathematics teachers, especially mathematics teachers in SMA Negeri 15 Medan to be able to use two pieces of mathematical software namely MAPLE and GEOGEBRA so that the competencies of these mathematics teachers increase and be more updated with technology.